Current and future prospects of guggul: A critically endangered medicinal plant - Suthar, Manish Kumar; Mittal, Manish Kumar; Das, Manish (Indian Horticulture, 2023)
Conservation of Commiphora wightii, a critically endangered plant species, commonly known as Indian bdellium or guggul, is crucial due to its ecological and medicinal significance. This small deciduous tree species is native to India and plays a vital role in various ecosystems, and highly valued for its resin, which has been used for centuries in traditional Indian medicine, particularly in Ayurveda.Consequently, it has gained recognition worldwide, leading to high demand and excessive exploitation. The conservation of guggul is essential to ensure the species’ long-term survival and maintain ecological balance.